De Novo Genome Assembly of the Meadow Brown Butterfly, Maniola jurtina. Issue 5 (1st May 2020) - Singh, Kumar Saurabh; Hosken, David J; Wedell, Nina; ffrench-Constant, Richard; Bass, Chris; Baxter, Simon; Paszkiewicz, Konrad; Sharma, Manmohan D
Abstract: Meadow brown butterflies ( Maniola jurtina ) on the Isles of Scilly represent an ideal model in which to dissect the links between genotype, phenotype and long-term patterns of selection in the wild - a largely unfulfilled but fundamental aim of modern biology. To meet this aim, a clear description of genotype is required. Here we present the draft genome sequence of M. jurtina to serve as a founding genetic resource for this species. Seven libraries were constructed using pooled DNA from five wild caught spotted females and sequenced using Illumina, PacBio RSII and MinION technology. A novel hybrid assembly approach was employed to generate a final assembly with an N50 of 214 kb (longest scaffold 2.9 Mb). The sequence assembly described here predicts a gene count of 36, 294 and includes variants and gene duplicates from five genotypes. Core BUSCO (Benchmarking Universal Single-Copy Orthologs) gene sets of Arthropoda and Insecta recovered 90.5% and 88.7% complete and single-copy genes respectively. Comparisons with 17 other Lepidopteran species placed 86.5% of the assembled genes in orthogroups. Our results provide the first high-quality draft genome and annotation of the butterfly M. jurtina .